Evaluation and comparative analysis of the results of a vertical jump between young basketball and handball players - Aksovic, N.; Bjelica, B.; Milanovic, F.; Cicovic, B.; Bubanj, S.; Nikolic, D.; Skrypchenko, I.; Rozhechenko, V.; Zelenovic, M. (Pedagogy of Physical Culture and Sports, 2022)
Background and Study Aim. Team sports, basketball and handball, as well as their competitions, are very popular throughout the world. The aim of this research was evaluation and comparative analysis of the results of a vertical jump between young basketball and handball players. Material and Methods. A group of 37 participants took part in the research: 21 basketball players from the basketball club OKK ''Novi Pazar'' (age: 15.5 ± 0.5) from Novi Pazar formed the first subgroup and 16 handball players from the handball club RK ''Železnicar 1949'' (age: 25.4 ± 5.8; body height = 193.5 ± 7.5 cm; body weight = 94.0 ± 7.4 kg; body mass index = 25.03 ± 2.38 kg/m2) from Niš formed the second subgroup. Explosive power of the vertical jumps was assessed by the following tests: countermovement jump, countermovement jump/arm swing, squat jump. Participants had at least 5 years of training experience and held similar acute training histories prior to study commencement, completing 4 weeks of baseline conditioning during the general preparatory phase. Participants were free of injury, illness and disease as determined by a team physician prior to study participation. Results. The results of the independent samples t-test show that there were no significant differences (p > 0.05) between basketball and handball players in all vertical jump tests. Conclusions. This article contains new information about vertical jumps of young male basketball and elite male handball players that could be extremely useful for coaches. Also, these findings suggest that basketball coaches may benefit from talents` identification in young basketball players.